The Contribution of Agricultural Vocabulary Mastery to Argumentative Text Writing Skills - Aminarti; Dewi Anggraini; Nursaid; Yulianti Rasyid (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
The purpose of this study is to describe: 1) agricultural vocabulary mastery; 2) argumentative text writing skills; and 3) the contribution of agricultural vocabulary mastery to argumentative text writing skills. This study used a descriptive-quantitative method through simple regression. The population of this study was 81 students of grade XI of SMA Negeri 1 Pasaman who took the agricultural vocabulary mastery test and the argumentative text writing skills test. The sample size was 68 students based on a statistical formula. To determine the effect of agricultural vocabulary mastery on argumentative text writing skills, a simple regression test procedure was used after conducting homogeneity and normality tests of residuals. The results of the study: 1) the vocabulary mastery of grade XI students of SMA Negeri 1 Pasaman was in good qualifications with an arithmetic mean of 80.44; 2) the argumentative text writing skills of grade XI students of SMA Negeri 1 Pasaman were in good qualifications with an arithmetic mean of 77.45; 3) The mastery of agricultural vocabulary of class XI students of SMA Negeri 1 Pasaman contributes significantly to the argumentative text writing skills of class XI students of SMA Negeri 1 Pasaman in the regression equation: Y = 7.443 + 0.513X1. This means that the value of the argumentative text writing skill variable for each sample member is a constant of 7.443 + 0.513 multiplied by the agricultural vocabulary mastery score of each student. Thus, Indonesian language teachers are expected to be able to carry out activities with various strategies and media to improve students' mastery of agricultural vocabulary.